From Resistance to Sensitivity: Insights and Implications of Biphasic Modulation of Autophagy by Sunitinib - Abdel-Aziz, Amal Kamal; Abdel-Naim, Ashraf B.; Shouman, Samia; Minucci, Saverio; Elgendy, Mohamed (Frontiers in Pharmacology, 2017)
Sunitinib, a multityrosine kinase inhibitor, is currently the standard first-line therapy in metastatic renal cell carcinoma and is also used in treating patients with pancreatic neuroendocrine and imatinib-resistant gastrointestinal stromal tumours. Nevertheless, most patients eventually relapse secondary to intrinsic or acquired sunitinib resistance. Autophagy has been reported to contribute to both chemo-sensitivity and -resistance. However, over the last few years, controversial regulatory effects of sunitinib on autophagy have been reported. Since gaining insights into the underlying molecular insights and clinical implications is indispensible for achieving optimum therapeutic response, this minireview article sheds light on the role of a network of prosurvival signaling pathways recently identified as key mediators of sunitinib resistance with established and emerging functions as autophagy regulators. Furthermore, we underscore putative prognostic biomarkers of sunitinib responsiveness that could guide clinicians towards patient stratification and more individualized therapy. Importantly, innovative therapeutic strategies/approaches to overcome sunitinib resistance both evaluated in preclinical studies and perspective clinical trials are discussed which could ultimately be translated to better clinical outcome.